A cooperation project between hospital pharmacists and general practitioners about drug interactions in clinical practice. Issue 6 (1st August 2017) - Vinciguerra, Valeria; Fantozzi, Roberto; Cena, Clara; Fruttero, Roberta; Rolle, Carla
Abstract : Objectives: (1) To evaluate drug–drug interactions (DDIs) in general practitioners' (GPs) prescriptions; (2) to implement a cooperation project between pharmacists and GPs to improve DDI management and patient care. Methods: In 2013, pharmacists from the Community Drug Assistance ASL TO1 launched a cooperation project involving 48 GPs. As a first step, GPs were asked to select, from a list, drug associations for which they recommended analysis of occurrence in their prescriptions. The pharmacists (1) analysed GPs' prescriptions dated 2012–2014, according to the list of DDIs selected (n= 9); (2) evaluated solutions for DDI management, using the Micromedex DDI checker database and literature analysis; they then (3) disseminated DDI-related information to GPs through training meetings and (4) assessed the efficacy of these actions through a questionnaire submitted to the GPs in 2013. Results: (1) Prescriptions analysis : a reduction in the number of DDIs was observed (−14% in 2013 vs 2012, –9% in 2014 vs 2012); in some cases these reductions were statistically significant (calcium carbonate + proton pump inhibitors (PPIs) −50%, p<0.0041, amoxicillin+lansoprazole −42%, p<0.0088). (2) Questionnaire : this was completed by 75% of GPs. The literature analysis was considered interesting by 94% of GPs; solutions were adopted by 89% of GPs and 34% of GPs affirmed that clinical improvements after application of the measures were observed in their patients, even if they could not provide quantitative data for this outcome. Conclusion: The cooperation project between pharmacists and GPs was effective because it established a professional exchange between the two health professionals. The pharmacist gave support to GPs, which benefited the patients, who gained clinical improvements and improved satisfaction with their medical care, as declared by the GPs in answers to the questionnaire.